INFLUENCE OF HIV INFECTION AND ANTIRETROVIRAL THERAPY ON AORTIC STIFFNESS: A META-ANALYSIS. (June 2018) - Mule', G.; Mule', G.J.; Geraci, G.; Colletti, P.; Mazzola, G.; Colomba, C.; Cottone, S.; Cascio, A.
Abstract : Objective: A growing body of evidence indicates that risk of CV events is higher in HIV-infected patients (HIV+) when compared to HIV-uninfected persons (HIV-). This enhanced risk may in part be mediated through preclinical CV damage. Large artery stiffness, a well-documented marker of arterial damage and predictor of adverse CV prognosis, is usually assessed by measuring aortic pulse wave velocity (PWV). Several studies examined arterial stiffness in HIV+ with inconsistent results. In a previous meta-analysis, showing increased arterial stiffness in HIV+ than in HIV- subjects, studies assessing aortic and peripheral PWV were pooled together. This may be misleading, because only the former has a demonstrated prognostic significance. We performed a new meta-analysis with the aim to evaluate the influence of HIV-infection and its therapy only on aortic PWV (aPWV). Design and method: A literature search was performed in PubMed, Google Scholar, Web of Science and Medline for articles, also in abstract form, concerning the effect of HIV infection and ART on aortic stiffness. The standardized mean difference (SMD) and corresponding 95% confidence intervals were calculated for aortic PWV in different comparison groups, which contained naive HIV+ versus HIV-, HIV+ receiving ART versus HIV- and HIV+ receiving ART versus naive HIV+. Statistical heterogeneity, assessed by Q test and I2 statistic, was observed in all these comparisons. Therefore, both the fixed and random effect models were implemented, even if only the results of the latter were presented. Results: In a total of 11 studies, naive HIV+ (n = 566) showed increased aPWV compared to HIV- (n = 816): SMD = 0.386 (0.197–0.575), p < 0.001. Nine studies were identified comparing HIV+ treated with ART (n = 631) to HIV- (n = 637) showing higher values of aPWV in the former than in latter: SMD = 0.681 (0.396–0.967), p < 0.001. In 8 studies HIV+ treated with ART (n = 599) exhibited greater aPWV values than those of naive HIV+ (n = 325): SMD = 0.259 (0.006–0.512), p < 0.04. Conclusions: Our meta-analysis seems to suggest that HIV infection per se and even more ART may impair aortic distensibility.